ANALISIS KUALITAS SDM DAN PELAYANAN PUBLIK BERBASIS DIGITAL TERHADAP KEPUASAN WAJIB PAJAK (Universitas Muhammadiyah Palembang, 2023)
Purpose–The purpose of this study was to analyze the quality of human resources and digital-based public services on the satisfaction of land and building tax payers at UPT Tengah BAPENDA Bandung City.Design/methodology–The type of research used is quantitative where this research uses nonprobability sampling method purposive sampling technique, the sample which is the object of research is 150 respondents. The method of data collection is by distributing questionnaires which are then processed with the analytical methods used, namely validity testing, reliability testing, classical assumption testing, and hypothesis testing.Findings - The test results can be concluded that partially the quality of human resources has a positive and significant effect on taxpayer satisfaction, similarly to the quality of digital-based public services there is a positive and significant effect on taxpayer satisfaction. Simultaneously, it shows that the influence of the quality of human resources and the quality of digital-based public services affects the satisfaction of land and building taxpayers. The R Square value (coefficient of determination) is 0.772 or 77.7%. In other words, the variable taxpayer satisfaction can be explained or influenced by the variable quality of human resources and the quality of digital-based public services 77.7%, while the remaining 22.3% is influenced by other factors not examined.